Manajemen Pembelajaran Guru Dalam Meningkatkan Hasil Belajar Siswa Selama Pandemi Covid-19 - Ustadi Ustadi; Barnoto ,; Dewi Afiatul Qutsiyah (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
With the outbreak of the covid-19 pandemic, social dynamics are changing rapidly, including in the world of education. Where the transition of learning that was previously carried out face-to-face has shifted to a virtual space. The purpose of this study is to find out and analyze the planning, implementation and evaluation of online learning management at SDN Sawahan Mojosari during the pandemic.The type of research in this research is qualitative with a case study approach. Data collection techniques by means of observation, interviews and documentation. analysis using data reduction methods, data presentation and drawing conclusions. Techniques for data validity are credibility, transferability, dependability, and confirmability. The research results are. 1). The planning stage is carried out through several stages, namely first a small meeting of the principal with the school committee, as well as teachers, then the results of the meeting are socialized to parents and students 2). The implementation of online learning during the COVID- 19 pandemic at SDN Sawahan Mojosari was handed over to the implementation by the principal to each class teacher, namely by using the Whatsapp group Mapel, Google Classroom and Google Form to send materials, be it photos, videos, or LKPD 3). Evaluation of online learning during the COVID-19 pandemic at SDN Sawahan Mojosari was carried out by the Principal together with class teachers directly into the class group or through the teacher's personal WA